Vascular Ischemia as a Cause of Transient Global Amnesia: A Patient Series - GÜNGÖR TUNÇER, Özlem (Noro Psikiyatr Ars, 2015)
INTRODUCTION: Epileptic, migrainous, and vascular pathologies may cause transient global amnesia (TGA); however, the mechanism of causation remains unclear. We investigated possible vascular causes of TGA. METHODS: We retrospectively evaluated the clinical and radiologic studies of 13 patients with TGA. On admission, patients underwent diffusion-weighted imaging (DWI) and intra- and extracranial magnetic resonance angiography (MRA); vascular risk factor profiles for diabetes, hypertension, and hyperlipidemia; electroencephalography; and neuropsychological tests. Seven patients underwent control DWIs 24 h after symptom onset. RESULTS: One patient had two punctiform acute infarcts in the left hippocampus, and one had a left pontine paramedian acute infarct. In the second patient, control DWI showed additional left hippocampal and right frontal acute infarcts. None of the patients had electroencephalographic evidence of epileptic activity. All patients except for one had at least one vascular risk factor. The second patient was shown to have paroxsysmal atrial fibrillation during follow-up. CONCLUSION: Minor posterior circulation ischemic stroke appears to cause TGA in some patients. Evaluations such as DWI and vascular risk factor assessment may be helpful in making the diagnosis.